Effect of B-complex supplementation on professional football players - Cannataro, R.; Bonuccelli, A.; Gatteschi, L.; Cione, E.; Stefanini, L.; Semperboni, L.; Bartoli, S.; Angelini, F.; Cicero, A. F. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The use of supplements in professional sport is still a controversial subject; there is a discussion on the advisability of their use regarding the improvement of performance, as well as on the definition of ad hoc ranges that should be different from those of the normal population, which guarantee that there are no deficits and therefore possible pathologies; for example, the RDA of vitamin C guarantees not to have scurvy, but the goal of nutrition applied to the sport should guarantee an optimal value not only to preserve from possible pathological states.